2018
DOI: 10.1016/j.nbd.2017.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid synthesis by NG2 expressing cells promotes a permissive environment for axonal outgrowth

Abstract: Stimulation of retinoic acid (RA) mediated signalling pathways following neural injury leads to regeneration in the adult nervous system and numerous studies have shown that the specific activation of the retinoic acid receptor β (RARβ) is required for this process. Here we identify a novel mechanism by which neuronal RARβ activation results in the endogenous synthesis of RA which is released in association with exosomes and acts as a positive cue to axonal/neurite outgrowth. Using an established rodent model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 51 publications
0
35
0
Order By: Relevance
“…These results suggest that RALDH2 is mainly expressed in a subset of PDGFR␤ ϩ cells in the postnatal brain. Moreover, several studies have observed RALDH2 expression in NG2ϩ glia and mature OLs following spinal cord injury (Mey et al, 2005;Kern et al, 2007;Goncalves et al, 2018), thus implicating RALDH2-dependent RA synthesis in NG2 ϩ cells in OPC differentiation following injury. However, our examination of expression profiles databases generated by recent single cell RNA sequencing studies aimed at characterizing OL lineage cell progression and heterogeneity in the adult CNS revealed that Raldh2 was not expressed highly by any cell in the OL lineage (Marques et al, 2016(Marques et al, , 2018.…”
Section: Raldh2 Expression In the Postnatal Mouse Brainmentioning
confidence: 99%
“…These results suggest that RALDH2 is mainly expressed in a subset of PDGFR␤ ϩ cells in the postnatal brain. Moreover, several studies have observed RALDH2 expression in NG2ϩ glia and mature OLs following spinal cord injury (Mey et al, 2005;Kern et al, 2007;Goncalves et al, 2018), thus implicating RALDH2-dependent RA synthesis in NG2 ϩ cells in OPC differentiation following injury. However, our examination of expression profiles databases generated by recent single cell RNA sequencing studies aimed at characterizing OL lineage cell progression and heterogeneity in the adult CNS revealed that Raldh2 was not expressed highly by any cell in the OL lineage (Marques et al, 2016(Marques et al, , 2018.…”
Section: Raldh2 Expression In the Postnatal Mouse Brainmentioning
confidence: 99%
“…Synaptophysin-positive clusters indicative of a 'classical' secretory vesicle accumulation and release machinery have been observed at defined sites along the NG2 glia processes [41]. Other mechanisms of signal transfer have been also reported, including cleavage of fragments of membrane-bound molecules [98] or exosome shedding [99]. Signal transfer through exosomes allows cell-specific targeting by receptor-ligand interactions [100] and assures that a well defined concentration of the signal may be delivered to the target.…”
Section: Ng2 Glia-derived Signals Can Modulate Neuronal and Non-neuromentioning
confidence: 97%
“…study of freshly sorted adult human NG2 glia [125] Neuronal survival [181] Bone morphogenic protein 7, BMP7 Gene expr. study of freshly sorted adult human NG2 glia [125] Maintainance of the identity of catecholaminergic neurons and differentiation of astrocytes [182] Retinoic acid, RA Application of pharmacological inhibitors in cultured mouse NG2 glia and in vivo assays in a model of rat spinal cord injury [99] NG2 glia regulation of axonal outgrowth [99] Slit1 Gene expr. study of freshly sorted adult human NG2 glia [125] Regulation of adult SVZ neurogenesis [183], axon outgrowth and glial scar formation [184] Inflammatory cytokines/ immunomodulatory factors Interleukin 1 beta, Il-1b Gene expr.…”
Section: Neuregulinsmentioning
confidence: 99%
See 1 more Smart Citation
“… 44 In addition, cells expressing Neuron-Glia 2 (NG2 cells) which are often perceived as having a axonal growth inhibitory effect, in response to C286 24 act as pathfinders to the growing axon and then differentiate into myelinating oligodendrocytes. 45 They achieve this by expressing the retinaldehyde dehydrogenase 2 (RALDH2) enzyme which synthesises retinoic acid (RA). The precursor of RA, retinal is induced by C286 24 in the neurons by stimulating the expression of alcohol dehydrogenase (ADH) IV, the retinal is then transferred across to the NG2 cells which is then converted into RA.…”
Section: Rarβ Agonistsmentioning
confidence: 99%